Review Artikel : Rute Pemberian Terbaik dari Sistem Penghantaran Obat Menuju Sistem Syaraf Pusat dari Berbagai Rute Pemberian - Andi Permana; Alisya Nabila Agustin; Intan Nurlaili Izzah; Nisa Nur Azizah; Selviani Eka Suci; Tita Ruhdiana6; Nia Yuniarsih (Poltekkes Kemenkes Medan, 2022)
The development of methods to improve drug delivery for use in life-threatening diseases such as cancer and viral infections is urgently needed. Some drugs that have a drug delivery system to the central nervous system are mostly into active targeted delivery. The central nervous system is related to the human nervous system which is a complex, highly specialized and interconnected network of nerves. The functions of the nervous system include: coordinating, interpreting and controlling the interaction between the individual and the surrounding environment. The purpose of this review article is to find out the best route of drug administration from several routes of administration to get the best injection route, but the optimal route for delivery to the brain may depend on the underlying disease being treated.